2013
DOI: 10.1089/thy.2012.0103
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Sorafenib in Patients with Advanced Anaplastic Carcinoma of the Thyroid

Abstract: Sorafenib has activity in ATC, but at a low frequency and similar to our previous experience with fosbretabulin. One patient with a response had previously progressed on fosbretabulin. Toxicities were both predictable and manageable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(134 citation statements)
references
References 19 publications
(21 reference statements)
2
120
1
5
Order By: Relevance
“…Our findings show that the NIR NP platform can facilitate the in vivo delivery of siBRAF into ATC xenograft tumors, eliciting robust BRAF silencing in the tumor tissue and effective suppression of tumor growth without obvious side effects. Although several small molecule inhibitors of BRAF have recently been approved by the Food and Drug Administration for the treatment of late-stage melanoma with BRAF mutation, a phase II trial in patients with ATC has shown that the BRAF inhibitor sorafenib only modestly extends overall survival and allows relapse (29), largely because of the inevitable drug resistance. In addition, because of the need for long-term administration of inhibitors, patients often develop significant side effects, such as arthralgia, skin rash, and photosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that the NIR NP platform can facilitate the in vivo delivery of siBRAF into ATC xenograft tumors, eliciting robust BRAF silencing in the tumor tissue and effective suppression of tumor growth without obvious side effects. Although several small molecule inhibitors of BRAF have recently been approved by the Food and Drug Administration for the treatment of late-stage melanoma with BRAF mutation, a phase II trial in patients with ATC has shown that the BRAF inhibitor sorafenib only modestly extends overall survival and allows relapse (29), largely because of the inevitable drug resistance. In addition, because of the need for long-term administration of inhibitors, patients often develop significant side effects, such as arthralgia, skin rash, and photosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Savvides et al conducted a phase II trial of another tyrosine kinase inhibitor, sorafenib, in patients with advanced ATC, and they reported that 2 of 20 patients (10%) showed a partial response [20].…”
Section: Discussionmentioning
confidence: 99%
“…Other than pazopanib, several other TKIs have been studied in the treatment of ATC but almost exclusively in phase 2 studies (Savvides et al 2013). The major limit of these studies is that the rarity of ATC that does not allow trials to enroll large numbers of patients in a short period of time.…”
Section: :4mentioning
confidence: 99%